Réponses

Meilleure réponse !
2013-02-24T16:11:00+01:00

A = (2x-3)² -(4x+7)(2x-3)

A = (4x² -12x +9) - ( 8x² -12x +14x -21)

A = (4x² -12x +9 - ( je simplifie l'expression avant de changer les signes car tu as un signe - devant la parenthèse)

                                  (8x² +2x -21)

A = 4x² -12x +9 -8x² -2x +21

A = -4x² -14x +30

 

x=5

A= ( (2x-3)² - (4x+7)(2x-3)

A = (2 X 5)² -( 4 X 5 +7)(2X 5 -3)

A = 10²       - (20 +7) (10 -3)

A = 10² - (27)(7)

A = 100 -189 = -89

 

pour x= V5 = 5 donc c'est idem